Effectiveness Probiotics as Anti-Aging for Facial Skin: A Systematic Review - Putu Adinda Novyta Arsha Putri; Ida Ayu Manik Partha Sutema; I Putu Gede Adi Purwa Hita; I Gusti Ayu Rai Widowati (Journal of Pharmascience, 2026)
Premature skin aging is increasingly prevalent among individuals in their mid-20s to 30s, influenced by genetic, lifestyle, and environmental factors. Probiotics have emerged as a promising natural intervention to address this issue. This systematic review aimed to evaluate the effectiveness of oral and topical probiotics in preventing and managing signs of premature skin aging. A systematic search of PubMed and Scopus was conducted for Randomized Controlled Trials (RCTs) published between 2020 and 2025, using PICO-based inclusion and exclusion criteria. Methodological quality was assessed with the JBI checklist. Of 202 articles screened, eight RCTs were included. Results showed that oral probiotics improved skin quality by enhancing collagen production (24%), hydration (18%), and antioxidant activity, while topical probiotics reduced wrinkles (22%) and increased skin density (15%). In conclusion, oral and topical probiotics represent effective dual strategies for combating premature skin aging, though further studies are needed to optimize strain-specific formulations.